Lethal infection by herpes simplex virus 1 (HSV-1) in a captive Azara’s owl monkey (Aotus azarae) in Paraguay - Vetter, J. Richard; Florentín-Morel, Marlene; Riera-Domínguez, María-Graciela; Cañiza, Ricardo G (Revista Colombiana de Ciencias Pecuarias, 2024)
Anamnesis: A 2-year-old male Aotus azarae was brought to the wild animal clinic. The animal weighed 975 grams and was in poor body condition. The individual had been kept in close contact with the caretakers and was largely fed by the people in the household, sharing their meals. According to the caretaker, the animal had been asthenic and anorexic for approximately two days. Clinical and laboratory findings: On clinical inspection, the animal was weakened, with pale oral mucosa, hyperemic pharynx, and a rectal temperature of 34.2°C. Dry crusts were observed in the perinasal region, and mild dyspnea was perceived. The patient died during the inspection. The hemogram was suggestive of normocytic normochromic anemia, leukopenia, hypoproteinemia, and thrombocytopenia. Molecular analysis detected HSV-1. Conclusion: Data obtained through anamnesis and clinical history, as well as hematologic findings and PCR results, confirmed the diagnosis of HSV-1 infection. To the best of the authors’ knowledge, this is the first report of the disease in a non-human primate in Paraguay.